2015
DOI: 10.1097/ta.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

The role of computed tomographic scan in ongoing triage of operative hepatic trauma

Abstract: Care management/therapeutic study, level IV; epidemiologic/prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…After laparotomy, persistent transfusion requirements usually suggest need for angiography and embolization. In this setting additional imaging can be helpful, as early post-operative CT has been found to determine which patients would require post-laparotomy angioembolization with high sensitivity and specificity 56 .…”
Section: Discussionmentioning
confidence: 99%
“…After laparotomy, persistent transfusion requirements usually suggest need for angiography and embolization. In this setting additional imaging can be helpful, as early post-operative CT has been found to determine which patients would require post-laparotomy angioembolization with high sensitivity and specificity 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Multidetector computed tomography plays a pivotal role in triaging for the angiography in patients with active arterial hemorrhage and pseudoaneurysm both before and in early postoperative phase 34 (Figure 11). The importance of active extravasation of contrast has been demonstrated in multiple studies, and usually, its presence indicated urgent surgical intervention.…”
Section: Approach To Visceral Injuriesmentioning
confidence: 99%
“…In patients with abdominal trauma who are hemodynamically stable, CT with intravenous contrast material is the imaging modality of choice (17), but the optimal use of imaging in patients undergoing DCS without preoperative imaging is an area of continued study (18)(19)(20)(21)(22)(23). A CT examination performed in the early perioperative period may allow identification of injuries that require additional intervention or occult injuries in or beyond the surgical field and may provide the potential to change the patient treatment plan.…”
Section: Imaging After Dcsmentioning
confidence: 99%
“…A CT examination performed in the early perioperative period may allow identification of injuries that require additional intervention or occult injuries in or beyond the surgical field and may provide the potential to change the patient treatment plan. Recent studies have shown that approximately 10%-30% of patients who undergo DCS undergo CT within 48 hours of surgery (19,(21)(22)(23).…”
Section: Imaging After Dcsmentioning
confidence: 99%
See 1 more Smart Citation